PRODUCTION AND CHARACTERIZATION CHITOSANASE OF SPONGE - Sarni Sarni (Hasanuddin University, 2016)
Chitosanase enzyme is an enzyme to catalyze the bonding endohidrolisis (1.4) β- glucoside on chitosan into a series chitosan oligomers or chitooligosaccarides. Chitosanase of microbes give good results in producing chitooligosaccarides, but very expensive for use in large-scale industry. This study aims to manufacture and characterization of crude chitosanase enzyme from Klebsiella sp used to hydrolyze chitosan into chitooligosaccarides. Chitosanase produced in the fermentation medium containing 0.5% colloidal chitosan for 60 hours with the activity of 0.309 U / mL (5,235 U / mg), work optimally at 40 ° C and pH 8, is stable at pH 6-7, activated by Co2 + ; Ca 2+ and Ni 2+. Chitooligosaccarides obtained in the form of a mixture of monomer to octamer, which soluble in acetic acid 0.25% to 0.5%, having intrinsic viscosity decreases with increasing time of incubation with molecular weight range of 4103.12 g / mol (incubation 1 hour) ; 1483.48 g / mol (incubation 2 hours) and 1065.79 g / mol (incubation 3 hours).Key word : Chitosanase, Klebsiella, Chitooligosaccarides